Reklamasi Revegetasi pada Area Pertambangan Nikel PT Aneka Tambang (Persero) Tbk. di Pomalaa, Kabupaten Kolaka, Sulawesi Tenggara - Kusdarini, Esthi; Yopianus, Benyamin; Bahar, Hendra (Dinamika Lingkungan Indonesia, 2024)
Nickel mining activities carried out by PT. Aneka Tambang (Persero) Tbk cause changes in the shape and function of the land. Land needs to be restored to its function after mining ends. The restoration of land function is carried out through reclamation activities. This study aims to plan reclamation activities in the mining area. The research methods used are field observation, interviews, secondary data collection, and mathematical calculations. The results of the study indicate that the reclamation activity plan on an area of 88,000 m2 uses the revegetation method. The covercrop plants used are cogongrass. Land use of the terrace system requires 52,800 m3 of topsoil (topsoil thickness 0.6 m). Meanwhile, erosion and landslide control is carried out by making water channels, sumps, and settling ponds. The dimensions of the sump are (1.5 x 1.5 x 1.5) m. Revegetation is planned to use 4 types of local plant seeds, namely 9,777 sea pines; red callindra 3,359 fruits, bitti 3,359 fruits, and forest mango 3,259 fruits. The distance of planting the main plant of sea pine is 3 x 3 m, while the distance of planting other local plants is 1.5 x 1.5 m. Furthermore, for maintenance, 48,885 kg of manure is needed. The findings of the research results help the company in planning reclamation activities and minimizing erosion and landslides in the reclamation area.